2022
DOI: 10.1093/ageing/afac116
|View full text |Cite
|
Sign up to set email alerts
|

Association of prediabetes with death and diabetic complications in older adults: the pros and cons of active screening for prediabetes

Abstract: Background active screening can improve health outcomes for people with prediabetes. However, its efficacy in older adults remains uncertain. Objective the study aimed to analyse the progression from prediabetes to diabetes in older adults, including associated complications and mortality rates, to determine the benefits of active screening. Design retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Our data provide valuable insights for health administrators regarding public resource allocation. We found that the risk of mortality was consistently increased in the IFG group, with a HR of 1.06 and 95% CI of 1.05 to 1.07, which aligns with a recent report [ 22 ]. Approximately 50% of the elderly population falls under the IFG category [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data provide valuable insights for health administrators regarding public resource allocation. We found that the risk of mortality was consistently increased in the IFG group, with a HR of 1.06 and 95% CI of 1.05 to 1.07, which aligns with a recent report [ 22 ]. Approximately 50% of the elderly population falls under the IFG category [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…In South Korea, almost 20% of adults aged ≥ 65 years with prediabetes progress to diabetes. In addition, in adults aged ≥ 75 years diagnosed with prediabetes or diabetes, the risk of diabetic complications did not increase [ 33 ]. However, in the current study, we included all adults aged ≥ 20 years, including older adults, to evaluate the effectiveness of screening for diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Prediabetes is a growing public concern leading to serious vascular consequences [ 1 , 2 ]. It was estimated that prediabetes affects 470 million people worldwide by 2030, who would suffer from end-organ damages in heart, brain, kidney, and eye before the diagnosis of diabetes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional lifestyle and drug-based interventions did no significantly reduce the risk of vascular complications among prediabetic individuals, such as myocardial infarction and stroke [ 5 ]. Development of new strategy to prevent vascular complications are urgently needed for people with prediabetes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%